2000
DOI: 10.1093/sleep/23.6.1a
|View full text |Cite
|
Sign up to set email alerts
|

EEG Bands During Wakefulness, Slow-Wave and Paradoxical Sleep as a Result Of Principal Component Analysis in Man

Abstract: Human electroencephalogram (EEG) has been divided in bands established by visual inspection that frequently do not correspond with EEG generators nor with functional meaning of EEG rhythms. Power spectra from wakefulness, stage 2, stage 4 and paradoxical sleep of 8 young adults were submitted to Principal Component Analyses to investigate which frequencies covaried together. Two identical eigenvectors were identified for stage 2 and stage 4: 1 to 8 Hz and 5 to 15 Hz (87.95 and 84.62 % of the total variance res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 32 publications
(53 reference statements)
1
32
0
Order By: Relevance
“…EEG is artificial (Corsi-Cabrera et al, 2000). Our results suggest that a well-defined range of delta activity (1.5-3 Hz) in temporolateral leads is a basic characteristic of REM sleep, but has different sources from that of NREM delta oscillation.…”
Section: __________________________________________________ Hippocampmentioning
confidence: 71%
“…EEG is artificial (Corsi-Cabrera et al, 2000). Our results suggest that a well-defined range of delta activity (1.5-3 Hz) in temporolateral leads is a basic characteristic of REM sleep, but has different sources from that of NREM delta oscillation.…”
Section: __________________________________________________ Hippocampmentioning
confidence: 71%
“…At least ten 2-s epochs were analyzed for each subject and condition. Previous studies have demonstrated that 10 epochs of 2 s of EEG satisfy both stationarity and stability for spectral analysis (Cohen, 1977;Mö cks and Gasser, 1984;Corsi-Cabrera et al, 2000). Signals were Fast Fourier transformed and power was averaged over 1 Hz to obtain EEG absolute power spectra (AP) with 1 Hz resolution from 1 to 50 Hz for each subject, physiological state and derivation.…”
Section: Methodsmentioning
confidence: 99%
“…According to original conceptions by Bente [8] and Roth [9] , the following EEG vigilance stages can be observed during the transition from high alertness to relaxed wakefulness to drowsiness and finally sleep onset: • Stage 0: desynchronized non-alpha EEG in the absence of slow horizontal eye movements; found during an activated state (e.g. mental effort) • Stage A (with substages A1, A2, A3): EEG with dominant alpha activity corresponding to relaxed wakefulness, with decreasing vigilance, slight slowing of alpha activity and shift from occipital to more anterior cortices • Stage B1: non-alpha EEG with low amplitude (similar spectral composition as stage 0) but with presence of slow horizontal eye movements; drowsiness • Stage B2/3: non-alpha EEG with predominant theta/ delta activity, occasional occurrence of vertex waves; drowsiness and transition to sleep onset • Stage C: commencing with occurrence of sleep spindles or K complexes; sleep onset More recent studies on changes of EEG activity during the transition from active wakefulness to sleep onset endorse this classification [36][37][38][39][40][41][42][43][44][45][46] .…”
Section: Assessment Of Wakefulnessmentioning
confidence: 98%